Knowledge, Attitude, Practice, Behavior and Risk Perception of COVID-19 Pandemic among Medical and non-Medical University Students. (10th January 2023) - Fatima, Madeeha; Habib, Aamna; Khan, Saira; Butt, Muhammad Hammad; Mallhi, Tauqeer Hussain; Khan, Yusra Habib; Zaheer, Asifa; Habib, Muhammad Umar; Khan, Abdul Qayyum; Khan, Muhammad Imran; Iqbal, Azhar; Mehmood, Malik Hassan; et al.
Abstract: Objective: Coronavirus disease 2019 (COVID-19) pandemic has substantially affected students around the globe due to the closure of educational institutes. However, student involvements and contributions are important in combating the disease; for this reason, the current study was designed to assess the knowledge-attitude-practice (KAP), preventive behavior, and risk perception among university students. Methods: A cross-sectional survey-based study was conducted among medical and non-medical university students, from April 1 to June 30, 2020. The 68-item questionnaire was used to evaluate responses using statistical approaches (Student's t-test, regression-analysis, and co-relation analysis) by considering a P -value <0.05 as statistically significant. Results: A total of 503 university students (medical and nonmedical) were selected, where majority of participants were females (83%) and 64.5% were of age ranged from 16 to 21 years old. The participants (80%) reported good disease knowledge with a mean score of 12.06 ± 1.75, which substantially higher among medical students ( P < 0.05). Most of the respondents (72%) believed that COVID-19 will be effectively controlled through precautionary measures. In correlation subgroup analysis, a significant relationship ( P = 0.025) between knowledge and positive attitude were indicated. Fear and knowledge of COVID-19 emerged as strong predictors ( P < 0.001) of preventive behaviors towards disease. Conclusion: This study demonstrated satisfactory knowledge, positive attitudes, and suitable practices among students toward COVID-19. University students can be involved in public education to aid the health authorities in achieving the targets of educational campaigns with maximum population coverage.